Preparation of Well-aligned CuO Nanorods by Thermal Oxidation Method - Ha, Tran Thi; Huyen, Bui Thi; Tuyen, Nguyen Viet (VNU Journal of Science: Mathematics - Physics; Vol 32 No 4, 2016)
Abstract: Well-aligned CuO nanorods were successfully prepared  by thermal oxidation method. The effect of annealing time and annealing temperature on the morphology of the nanorods were studied by scanning electron microscopy. The results show that annealing temperature plays a more critical role in affecting the diameter and density of nanorods. Besides SEM images, the effect of annealing time and temperatures on the structure of the product were also studied by X-ray diffraction and Raman spectroscopy. The diameter of CuO nanorods varies from 30 nm to above 100 nm when annealing temperature changes from 400 °C to 600 °C, while the length of the rods is up to several tens of  micrometers. The most uniform nanorods with highest crystal quality of CuO were obtained when annealing temperature is 500 °C and annealing time was 2 h as suggested by SEM images together with Raman results. Keywords: Cupric, Nanorods, Raman, Thermal oxidation.